2015
DOI: 10.1016/j.ultsonch.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

An extended model for ultrasonic-based enhanced oil recovery with experimental validation

Abstract: This paper suggests a new ultrasonic-based enhanced oil recovery (EOR) model for application in oil field reservoirs. The model is modular and consists of an acoustic module and a heat transfer module, where the heat distribution is updated when the temperature rise exceeds 1 °C. The model also considers the main EOR parameters which includes both the geophysical (i.e., porosity, permeability, temperature rise, and fluid viscosity) and acoustical (e.g., acoustic penetration and pressure distribution in various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 30 publications
0
24
0
8
Order By: Relevance
“…Some studies have been performed in the field of enhanced oil recovery using ultrasonic waves (Wang and Xu 2015;Wang and Zhou 2004). Experimental models for ultrasonic-based enhanced oil recovery have been presented and indicated that ultrasonic waves can greatly increase production (Mohsin and Meribout 2015;Wegener et al 2001;Amro et al 2007). Changes in crude oil characteristics due to ultrasonic wave irradiation are also evaluated (Shi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been performed in the field of enhanced oil recovery using ultrasonic waves (Wang and Xu 2015;Wang and Zhou 2004). Experimental models for ultrasonic-based enhanced oil recovery have been presented and indicated that ultrasonic waves can greatly increase production (Mohsin and Meribout 2015;Wegener et al 2001;Amro et al 2007). Changes in crude oil characteristics due to ultrasonic wave irradiation are also evaluated (Shi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is great interest in the development of more efficient technologies. Over the last few years, the use of physical EOR techniques have been reported, especially those based on ultrasonic treatment [11][12][13][14][15]. We have developed an ultrasound-assisted method that operates in the wellbore perforation zone with the simultaneous creation of a zone of lower pressure.…”
Section: Ultrasonic Technology For Enhanced Oil Recovery and Transportation Of Highly Viscous Oilmentioning
confidence: 99%
“…Overall the complexity of such process hindered theoretical modelling of ultrasonic enhanced oil recovery technique. For example, Mohsin and Meribout [36] developed a model which involves heat and acoustic modules to predict the performance of ultrasound on oil recovery in a single phase (oil) flow process and they tested their model with their experimental data. They also found that there was a pressure increase due to ultrasonic waves which led to improved oil recovery.…”
Section: Introductionmentioning
confidence: 99%